Subretinal Hemorrhage Associated With Scleral Buckle Surgery for Retinal Detachment A Consecutive Case Series - Pandiri, Srujay (Ophthalmic surgery, lasers & imaging retina, 2025)
BACKGROUND AND OBJECTIVE: This study aimed to analyze rates of subretinal hemorrhage (SRH), any correlations between SRH and drainage technique (scleral cutdown and external needle drainage) during scleral buckle (SB) surgery, as well as associated structural outcomes